KILKA UWAG O SĄDZIE KANCLERSKIM I SYSTEMIE EQUITY W ANGLII - Marzec, Łukasz (Zeszyty Prawnicze, 2017)
Remarks on the Court of Chancery and the Equity System in England Summary The Court of Chancery was a significant element in the English judicial system which operated outside the sphere of com m on law. Throughout hundreds o f years, the Court of Chancery developed a unique branch of equity law, which co-existed with the com m on law. This was very similar to the Roman ius civile and the praetorian law. Although the Court was abolished in the 19th century, its jurisdiction is still applied by the Chancery Division of the High Court of Justice. The equity law, intended to be a remedy for the strict rules of com m on law, borrowed much from the Roman law. M any chancellors and masters in Chancery, having obtained a D. C. L or LL. D degree were open to adopt Rom an law rules into the C ourt’s practice. In the opinion of some scholars, some of the equity rules were borrowed from the Rom an law, like trust (fideicomissum) or elements of mortgage (equity o f redemption). M any „rules of equity” have also their origin in the Roman jurisprudence.